Some Legal Issues Related to the Jurisdiction of the Court in the Framework of an Application for Permission to Conduct an Operational Search Event or a Secret Investigative Action - Amiryan, Karen (Bulletin of Yerevan University C: Jurisprudence, 2025)
The purpose of the article is to analyze some of the legislative requirements for the consideration of petitions submitted to the court for conducting an operational search event or a secret investigative action. The legal norms are such that often both the investigating authorities and the prosecutor’s office, as well as the court interpret them in different ways. This, in particular, refers to the interpretation of the result obtained during an operational search event or a secret investigative action, in accordance with one of the requirements imposed on these requests during requests for an extension of the period of an operational search event or a secret investigative action. In addition, there is still no unified approach in law enforcement practice regarding the obligation of a court considering a request for an operational search measure or a secret investigative action to identify a legislative gap existing in the RA Criminal Code. In other words, the article aims to present the problems that have arisen in law enforcement practice. In this regard, the article is also relevant, since the presented approaches may be of interest to both students and lawyers, law enforcement officers and judges.